HISTOPATOLOGI PLASENTA DAN TRANSMISI VERTIKAL PADA WANITA HAMIL DENGAN INFEKSI COVID-19 (CORONAVIRUS DISEASE 2019): Tinjauan Systematic Review - Ghina Nabila Aisyah (2021)
Coronavirus Disease 2019 (COVID-19) is an infectious respiratory disease that has become a pandemic since 2020. This disease is caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), it is an endotheliotropic virus, which can increase the risk of thrombosis on infected person. Pregnant women have physiological changes in their body that can help them prevent bleeding, this condition could increase the risk of thrombosis. In Indonesia, 536 cases of pregnant women were confirmed to be infected with COVID-19 in April 2020 - April 2021. Therefore, the aim of this study was to discover placental histopathology and vertical transmission in pregnant women with COVID-19 infection. Methods: A systematic review was done according to Preferred Reporting Items for Systematic Reviews and Meta-analyses Protocols (PRISMA-P) 2015. The database used was PubMed. There were 47 literatures which fulfilled the inclusion criteria. Results: Found 931 placentas with maternal vascular malperfusion (51,56%), fetal vascular malperfusion (46,83%), acute inflammatory responses: maternal (23,84%) and fetal (7,95%), chronic inflammatory responses (16,11%), other inflammatory responses (9,24%), and others placental conditions (39,20%) on placental histopathology. Twenty-eight journals discussed the vertical transmission of COVID-19 infections, in which 22 journals found no evidence, 5 journals showed cases that cannot be classified based on the criteria yet, and 11 journals can be classified based on Shah et al criteria. Conclusion: Placental histopathology could be maternal and fetal vascular malperfusion, acute and chronic inflammatory responses, other inflammatory responses, and others placental conditions. Vertical transmission of COVID-19 infection could happen, but the incidence is low.